Reading the Fire : The Traditional Indian Literatures of America - Ramsey, Jarold, 1937- (Book collections on Project MUSE., 1999)
"Reading the Fire engages America's "first literatures," traditional Native American tales and legends, as literary art and part of our collective imaginative heritage. This revised edition includes four new essays."--Jacket.